Association between family support and glycemic control among patients with type 2 diabetes mellitus who attend an endocrinology office of a public hospital - Abuhadba Miranda, Carlos (2021)
Objective: To determine the association between family support and glycemic control among patients with type 2 diabetes mellitus who attend the outpatient endocrinology office of the Hospital Nacional Dos de Mayo. Materials and methods: A quantitative, observational and cross-sectional study was carried out. The sample consisted of 158 diabetic subjects over 18 years of age whose glycosylated hemoglobin was obtained at the time of the consultation using the Epi Info version 7.9.2 software, with a 95 % confidence level, 5 % accuracy and 12.11 % expected frequency. A non-probability convenience sampling was used. A data collection sheet was employed to register the patients’ sociodemographic, clinical and social environment data, as well as the Family Adaptability and Cohesion Evaluation Scale III (FACES III) to determine the family support. A chi-square test was used to determine the association between family support and glycemic control. Results: Female patients accounted for 50.6 % (n = 80) of the sample. The mean age was 63.5 ± 12.10 years. The patients’ children (50.6 %, n = 80) and spouses (20.3 %, n = 32) were the most likely primary caregivers. Out of the 158 study subjects, 98 (62 %) had a good glycemic control, 44 % of whom (44.9 %) presented an adequate family support. Out of the 60 patients with no glycemic control, 16 (26.6 %) had an adequate family support. A statistically significant association between family support and glycemic control was demonstrated, with X² = 5,252 and ρ value < 0.05. Conclusions: There is a significant association between family support and glycemic control among the diabetic patients treated at the outpatient endocrinology office of the Hospital Nacional Dos de Mayo.